Modelling the Increased Risk of Malaria Due to Climate Change in Jayapura, Papua: An Ecological-Epidemiological Analysis of the Jayapura Coastal Area - Susanti; Rahayu Tri Nuritasari; Korinus Suweni; Yunita Kristina; Jernita Sinaga (CV. Get Press Indonesia, 2025)
Climate change is a major cause of morbidity and mortality in tropical and subtropical countries. In Indonesia, Papua is one of the provinces with a high malaria burden. However, there is limited empirical evidence on the relationship between climate and malaria in coastal areas. This study used an ecological-epidemiological study design with quantitative approach to analyze the relationships between climate variables and malaria incidence in coastal regions. The results showed that changes in climate variables significantly influence malaria incidence. Wind speed and sunshine duration were the most dominant and consistent factors influencing malaria incidence, in both linear and non-linear relationships. The GAM model provided the highest predictive performance compared to the GLM. The findings of this study imply that malaria early warning systems and climate change adaptation strategies require more flexible modeling approaches and the inclusion of non-conventional climate variables. This research also reinforces the need for the integration of climate and ecological data in public health policies, particularly in highly vulnerable coastal areas like papua.